Guinea Pig Model to Establish the Safety of Middle Ear Pellets. (2nd September 2014) - Hoskison, Emma E.; Daniel, Matija; Qureishi, Ali; Lee, Y. S.; Mulheran, Mike; Bayston, Roger; Birchall, John P.
Abstract : Objectives: Effective treatments for otitis media with effusion (OME) remain elusive as many patients have recurrence. Direct drug delivery to the middle ear has the potential to maximize efficacy, minimize side effects, and provide a sustained release treatment, which is particularly important in the treatment of biofilms. Polymer‐based pellets are delivery vehicles for antibiotics and pellet placement in the middle ear is a potential future OME treatment. In vivo testing of these pellets in animal models is necessary prior to human application. Methods: Twenty‐four adult guinea pigs were divided into 3 (n = 8) treatment groups: biological controls, surgical controls, polylactic glycolic acid (PLGA) pellets inserted in middle ear. The surgical approach involved submandibular incision, dissection, and following digastric up to the middle ear bulla. Perforating the bulla wall facilitated a 2.5‐mm diameter pellet insertion. Auditory brainstem responses (ABRs) were recorded at 0, 1, 2, 4, and 16 weeks at 6 frequencies over 8 to 30 kHz. Analysis was performed using a paired t test with significance set at P <. 05 (Bonferroni correction). Results: Mean ABR thresholds across the 3 groups ranged between 42 and 49 dB SPL over 4 weeks. There were statistically significant threshold elevations between 4‐10db SPL in the surgical control and pellet groups although these were not considered physiologically significant. Conclusions: Using a guinea pig model, PLGA pellet insertion into the middle ear caused ABR threshold elevation of only 4‐10 dB SPL, supporting their use as a potential vehicle for middle ear drug delivery.